TCF7L2 polymorphisms and inflammatory markers before and after treatment with fenofibrate. - Kabagambe, Edmond K.; Glasser, Stephen P.; Ordovas, Jose M.; Warodomwichit, Daruneewan.; Tsai, Michael Y.; Hopkins, Paul N.; Borecki, Ingrid B.; Wojczynski, Mary.; Arnett, Donna K. (2016)
Background: Inflammation is implicated in causing diabetes. We tested whether transcription factor 7 like-2 (TCF7L2) gene polymorphisms (rs12255372 and rs7903146), consistently associated with type 2 diabetes, are associated with plasma concentrations of inflammatory markers before and after three weeks of daily treatment with fenofibrate.; Keywords: Transcription factor 7 like-2, High sensitivity C-reactive protein, Interleukin-2, Interleukin-6, Tumor necrosis factor-α, Macrophage chemoattractant protein-1, Genetics of Lipid-Lowering Drugs and Diet Network.; Springer Open.